Unlocking Financial Literacy in Generation Z: Are Sociodemographic Factors the Key? - Adi Kurniawan Yusup; Charly Hongdiyanto (Petra International Journal of Business Studies, 2023)
This research aims to investigate the relationship between sociodemographic factors, encompassing age, gender, and access to the internet among Generation Z in Surabaya, utilizing the convergence theory framework. Convergence theory posits that both heredity and environmental factors can affect human development. There are 441 respondents employed as the sample of this research. We use multiple regression linear analysis to examine the hypothesis. The finding reveals that age and gender positively affect financial literacy, whereas access to the internet does not directly affect financial literacy. Instead, it exerts an indirect effect through financial interest. Various robustness tests were conducted, and the results remained consistent.